The Role of State Attorney in Prosecutor's Office of An Effort to Protect State Assets - Arrahim, Febri; Marjon, Dahlil; Syam, Misnar; Fauzan, Randi (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
This article examines the role of the State Attorney in Indonesia within the civil law sector, focusing on the safeguarding and recovery of state assets. With state assets dispersed across various institutions, the risk of losses necessitates adequate asset protection. The research addresses the legal standing and position of the State Attorney in the civil law field, as well as their duties in saving state assets. This paper analyzes applicable legal regulations and compares them with practical applications. Findings reveal that while the State Attorney possesses authority in law enforcement, legal assistance, and other legal actions, challenges impede the complete optimization of this authority. Despite obstacles, the Attorney General, through the State Attorney, plays a crucial role in defending the state's civil rights and securing state assets through civil instruments. The article highlights the need for greater awareness of the Prosecutor's Office in the civil sector, emphasizing its significance in representing the government and protecting state assets.